Aspirin-triggered resolvin D1 reduces parasitic cardiac load by decreasing inflammation in a murine model of early chronic Chagas disease. - Ileana Carrillo; Rayane Aparecida Nonato Rabelo; César Barbosa; Mariana Rates; Sebastián Fuentes-Retamal; Fabiola González-Herrera; Daniela Guzmán-Rivera; Helena Quintero; Ulrike Kemmerling; Christian Castillo; Fabiana S Machado; Guillermo Díaz-Araya; et al. (Public Library of Science (PLoS), 2021)
Background Chagas disease, caused by the protozoan Trypanosoma cruzi, is endemic in Latin America and is widely distributed worldwide because of migration. In 30% of cases, after years of infection and in the absence of treatment, the disease progresses from an acute asymptomatic phase to a chronic inflammatory cardiomyopathy, leading to heart failure and death. An inadequate balance in the inflammatory response is involved in the progression of chronic Chagas cardiomyopathy. Current therapeutic strategies cannot prevent or reverse the heart damage caused by the parasite. Aspirin-triggered resolvin D1 (AT-RvD1) is a pro-resolving mediator of inflammation that acts through N-formyl peptide receptor 2 (FPR2). AT-RvD1 participates in the modification of cytokine production, inhibition of leukocyte recruitment and efferocytosis, macrophage switching to a nonphlogistic phenotype, and the promotion of healing, thus restoring organ function. In the present study, AT-RvD1 is proposed as a potential therapeutic agent to regulate the pro-inflammatory state during the early chronic phase of Chagas disease. Methodology/principal findings C57BL/6 wild-type and FPR2 knock-out mice chronically infected with T. cruzi were treated for 20 days with 5 μg/kg/day AT-RvD1, 30 mg/kg/day benznidazole, or the combination of 5 μg/kg/day AT-RvD1 and 5 mg/kg/day benznidazole. At the end of treatment, changes in immune response, cardiac tissue damage, and parasite load were evaluated. The administration of AT-RvD1 in the early chronic phase of T. cruzi infection regulated the inflammatory response both at the systemic level and in the cardiac tissue, and it reduced cellular infiltrates, cardiomyocyte hypertrophy, fibrosis, and the parasite load in the heart tissue. Conclusions/significance AT-RvD1 was shown to be an attractive therapeutic due to its regulatory effect on the inflammatory response at the cardiac level and its ability to reduce the parasite load during early chronic T. cruzi infection, thereby preventing the chronic cardiac damage induced by the parasite.